Penggunaan Obat Tradisional Sebagai Terapi Komplementer Pada Pasien Hipertensi Di Puskesmas Gondokusuman I - artha utami (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2021)
Hypertension is a disease characterized by an increase in blood pressure. Hypertension therapy consists of pharmacological therapy and complementary therapy. Traditional medicine therapy is included in complementary therapy as a form of biologic therapy. This study aims to describe the use of traditional medicine as a complementary therapy in hypertension patients at the Gondokusuman I Public Health Center. This research is a type of descriptive research. Data collection was carried out in March 2021. The sample of this study amounted to 71 patients who were selected by total sampling. The subjects used in this study were hypertensive patients who were enrolled in the prolanis program at the Gondokusuman I Health Center. The exclusion criteria set were patients who did not use traditional medicine and patients who did not fill out the questionnaire completely. The data collection instrument used a validated questionnaire. Characteristics of patients using traditional drugs by gender are dominated by women (64.79%). The age of most traditional medicine users is 41-60 years old (66.20%). Housewives (22.54%) and retirees (22.54%) are the most users of traditional medicine by type of work. Patients suffering from hypertension for 4 years (33.80%) are the ones who use traditional medicine the most. Patients who use traditional medicine conventionally by concocting their own or blended by herbalists amounted to 32 patients. Meanwhile, 39 patients using traditional medicines processed by the drug industry. The industrially processed traditional medicines that were most consumed by patients with hypertension in this study were honey (33.3%), mangosteen peel extract (12.82%) and black cumin (12.82%). Meanwhile, the most widely consumed traditional medicines by concocting themselves are celery (12.50%) and garlic (12.50%)..